Drive-in torque for self-tapping screws into timber. Issue 1 (14th February 2022) - Zhang, Cong; Jung, Kiho; Harris, Richard; Chang, Wen-Shao
Abstract : Self-tapping screws have been widely used in timber constructions. The current practice considers self-tapping screws perform best in connecting two members when they are fully threaded; however, the drive-in resistance caused by the friction between the wood and the screw can potentially damage the screw and reduce the effectiveness of its applications. The relationship between their thread configuration and the drive-in torque force has not been investigated, and the question as to how would knots in the member affect the drive-in force, remains a unanswered. In this study a series of tests was conducted, aiming to demonstrate the influence of thread configuration on the drive-in torque of screws. Two types of self-tapping screws and three different thread configurations were studied. The drive-in torque for partially threaded screws was found to be significantly slower than that of fully threaded ones. The results showed that knots can significantly influence the positioning of the screw and increase the drive-in torque. The application of a pre-drilled hole was found to be an effective way to minimise the influence of knots. This paper points out that with appropriate consideration of thread configuration, partially threaded self-tapping screws can not only achieve the same efficiency as fully threaded ones, they will also benefit from reduced drive-in torque force.